Rūam botkhwām phư̄a kānpō̜ngkan læ fao rawang panhā yāsēptit (Samnak Phatthanā Kanpō̜ngkan læ Kǣkhai Panhā Yāsēptit, Samnakngān Pō̜. Pō̜. Sō̜., 2011)
Prevention and control measures of narcotics use by teenagers in Thailand.